Development of handouts on acid-base material with the sorogan learning method - Siska Widiana Putri; Rinaningsih Rinaningsih (Jurnal Pijar Mipa, 2023)
The Sorogan learning method is individual learning with the activities of students giving their learning outcomes (strong) to the teacher. This study aims to determine the feasibility of handouts in improving students' mastery of concepts in acid-base material using the developed Sorogan learning method in terms of validity, practicality, and effectiveness. The research for developing this handout refers to the Research & Development (R&D) development method, which is limited to the limited trial stage. Handout validity consists of content and construct validity. Content validity gets mode 5 with very valid criteria. Construct validity includes graphical, presentation, and linguistic criteria. Graphic criteria get mode 5 with very valid criteria, presentation criteria get mode 4 with valid criteria, and linguistic criteria get mode 4 with valid criteria. The practicality of the handout is seen from the results of observing the activities of the students by obtaining a percentage of 95.71% and the student response questionnaire in terms of the criteria for content, graphics, presentation, and language, getting a percentage respectively 98.33%, 96.67%, 97, 77%, and 100% with very practical criteria. The effectiveness of the handout is seen from the increase in pretest to posttest scores for each student using the N-Gain Score formula, and a value of <g> 0.8 is obtained, or it can be said to increase by 80% with high criteria. Classical completeness gets a percentage of 100% with very effective criteria. It shows that using handouts with the Sorogan learning method in acid-base chemistry learning can improve students' mastery of concepts and learning outcomes. The handout on acid-base material using the Sorogan learning method was declared feasible because it met the validity, practicality, and effectiveness criteria.